La fotografía artística, como elemento representativo de la realidad femenina, en el ambiente local - Matute Borrero, Maribel Alexandra (Machala, 2020)
Artistic photography, as a representative element of feminine reality, at the local level. Author: Maribel Alexandra Matute Borrero Tutor: Lcdo: Villota Garcia Franklin Renato. The present work called "Artistic photography, as a representative element of feminine reality, at the local level", reflects a problem that is very much dealt with today, which occurs frequently in our context. Artistic photography used as a form of visual representation to make known the reality of femicide and the macho society in which it is lived. Photography is the artistic modality used to represent the problem with specific objects that represent women, with a critical-reflective discourse that is welcomed by our society. Femicide is a problem that frequently exists in Ecuador, inequality between men and women is something that predominates in our country since the society in which we live is sexist and for this reason most men believe that they are superior women and that they have the right to whatever they deem appropriate. It is for this reason that we continue to live in this macho society that regardless of races, cultures or social classes, cases of femicide continue to occur and rise in the country and the world, regardless of the damage they do to children, leaving them many times with relatives and with a great psychological trauma since many of the times they observe these events. The function in a photograph is that it captures a real moment and thus shows that the field of visual arts is not only painting and drawing, but also has more modalities of how to show art. In this way, art opens the door for us to express and manifest with artistic works, that social problem that afflicts our society so much because there is no respect that it should towards women. With a critical-reflective language, this degree work tries to present femicide as latent events in our social environment. The purpose of this work is to reach society in a representative way through artistic photography and thus create a moment of reflection and awareness, so that the way of thinking about the way of treating women of our locality and the world. In this way, the purposes that were proposed are fulfilled so that this investigation could be carried out, as a first point, of analysis where it is inferred in the reflection on the murder of the women of the province of El Oro, managing to change the way of thinking of our town. As a second point, the application of photography as a means of artistic presentation in order to make society reflect and change its wrong way of seeing women. In this way, fulfilling the purposes that were proposed so that this investigation could be carried out, as a first point, of analysis where it is inferred in the reflection on the murder of the women of the province of El Oro, managing to change the way to think of our locality. As a second point, the application of photography as a means of artistic presentation in order to make society reflect and change its wrong way of seeing women. Since the woman is one of the most important bases for society because she is the procreator, the one who gives life to other human beings regardless of whether she is a man or a woman, for that time she should be treated in the same way as the rest of the world. society so that we can all see the true respect that exists for human beings.
La fotografía Artística, como elemento representativo de la realidad femenina, en el ámbito local. Autor Maribel Alexandra Matute Borrero Tutor Lcdo: Villota Garcia Franklin Renato. El presente trabajo denominado “La fotografía Artística, como elemento representativo de la realidad femenina, en el ámbito local”, refleja una problemática muy tratada en la actualidad la cual sucede frecuentemente en nuestro contexto. La fotografía artística usada como una forma de representación visual para dar a conocer la realidad del femicidio y de la sociedad machista en la que se vive. La fotografía es la modalidad artística utilizada para representar la problemática con objetos específicos que representan a la mujer, con un discurso crítico- reflexivo que sea acogido por nuestra sociedad. El femicidio es una problemática que existe en ecuador con frecuencia, la desigualdad entre los hombres y mujeres es algo que predomina en nuestro país ya que la sociedad en la que se vive es machista y por esta razón la mayoría de los hombre creen que son superiores a las mujeres y que tienen derecho a todo lo que ellos crean conveniente. Es por tal razón que seguimos viviendo en esta sociedad machista que sin importar razas, culturas o clases sociales sigue sucediendo y ascendiendo los casos de femicidio en el país y el mundo,sin importar el daño que le hacen a los niños dejándolos muchas veces con familiares y con un gran trauma psicológico ya que muchas de las veces ellos observan estos hechos. La función en una fotografía es que esta captura un momento real y así mostrar que el campo de las artes plásticas no solo es pintura y dibujo si no que tiene más modalidades de cómo mostrar el arte. De esta manera el arte nos abre la puerta para expresar y manifestar con obras artísticas, aquel problema social que aqueja tanto a nuestra sociedad porque no existe ese respeto que debería hacia la mujer. Con un lenguaje crítico- reflexivo este trabajo de titulación intenta presentar el femicidio como sucesos latentes en nuestro entorno social. El propósito del presente trabajo es de llagar a la sociedad de una manera representativa por medio de la fotografía artística y así crear un momento de reflexión y concientización, para que así cambie un poco la manera de pensar sobre la manera de tratar a las mujeres de nuestra localidad y del mundo. De esta manera se cumpliendo los propósitos que se planteó para que esta investigación se pudiera llevar a cabo, como primer punto, de análisis donde se infiere en la reflexión sobre el asesinato de las mujeres de la provincia de El Oro, logrando cambiar un poco la forma de pensar de nuestra localidad. Como segundo punto la aplicación de la fotografía como medio de presentación artístico para así hacer que la sociedad reflexione y cambie su forma errada de ver a la mujer. Ya que la mujer es una de bases más importantes para la sociedad porque ella es la procreadora, la que da la vida a otros seres humanos sin importar si es hombre o mujer, por tal rato ella debería ser tratada de igual manera que el resto de la sociedad y así todos podamos ver el verdadero respeto que existe sobre los seres humanos.
Keywords: MUJER; FOTOFRAFIA; MALTRATO; FEMICIDIO